THE TRANSLATION OF ENGLISH DERIVATIONAL BOUND MORPHEMES INDAN BROWN’S DECEPTION POINT INTO INDONESIAN TITIK MUSLIHAT - Wibowo, Agung Prasetyo; Suyudi, Ichwan (Universitas Gunadarma, 2014)
Morphemes as the smallest meaningful unit of a word has significant role in determining the meaning of the words. The translators must be able to translate the meaning of the morphemes accurate in order to keep the message faithful with the source text. The problems of this research are as follows: 1) what are the morphemic shifts occurred in the translation of English Derivational morphemes into Indonesian in Dan Brown’s Deception Point? 2) what are the principles employed by the translators? 3) what are the strategies employed by the translators? 4) what is the most dominant rank category? The aims of the study are as follows: 1) to find out the morphemic shifts occurred in Dan Brown’s Deception Point, 2) to find out the kinds of principles employed by the translators, 3) to find out the kinds of strategies employed by the translators, and 4) to find the most dominant rank category. The method employed in this research is descriptive-analytical method. The data of this study were collected from the words which contained English derivational bound morphemes in the novel Deception Point which is written by Dan Brown and its Indonesian translation entitled Titik Muslihat. The result of the research shows that 1) there are two kinds of morphemic shifts found.They are: shifts from morphemes to words and shifts from morphemes to phrases. 2) The principles of translation which are employed by the translators are meaning and source language influence. 3) The translation strategies which are employed by the translators are syntactic Strategy, Syntactic Strategy: Calque,Syntactic Strategy: Unit Shift,Semantic strategy: Distribution change. 4) The most dominant rank category found is morphemes which is translated into words category with 71% or 141 data. Key Words: Translation, English Derivational Bound Morphemes, Translation Theory, Principle of Translation, Translation Strategy.